Mechanism of realisation of state-private entrepreneurship in the social sphere of the Russian Federation - Stratan Dmytro I.; Hazuyev Ahmed I. (Problemi Ekonomiki, 2013)
The article states that the socio-economic development of a region rests on the higher-than-anticipated growth of its infrastructure. Formation of the social infrastructure of a region is based on practical realisation of social priorities directed at a higher satisfaction of needs of the population in social services. One of the mechanisms in development of social infrastructure is the state-private partnership. The article provides theoretical and methodical aspects of development of instruments of managing investment activity in Russian regions and levelling of territorial heterogeneity of availability of social objects on the basis of use of the state-private partnership (SPP). The article conducts assessment of possibilities of use of SPP models in the social sphere, regional economy and management of state property.